The Effect of Inflation and The Rupiah Exchange Rate on Stock Return - Januar, Ria Anggun; Afridayani, Afridayani (Universitas Pamulang, 2022)
This study aims to analyze the effect of inflation and the rupiah exchange rate on stock returns of property and real estate companies listed on the Indonesia Stock Exchange in 2015- 2020. The independent variables (independent) used in this study are Inflation and Rupiah Exchange Rate, while the dependent variable (dependent) is Stock Returns. The research method used is Descriptive Statistics, Classical Assumption Test, Hypothesis t-Test and Hypothesis F Test. The population in this study is 28 Properties and Real Estate Sector companies listed on the Indonesia Stock Exchange from 2015-2020. The selection of the research sample was based on the purposive sampling technique. Based on the results of the data analysis that has been carried out, it can be concluded that part there is an effect of Inflation on Stock Return, partially there is an effect of Rupiah Exchange Rate on Stock Return. And simultaneously there is the effect of Inflation and the Rupiah Exchange Rate on Stock Return